Manajemen Perawatan Pasien Kritis dengan Ketoasidosis Diabetikum di ICU - Jufan, Ahmad Yun; Widodo, Untung; Gafar, Wiramas Ikhsan (Jurnal Komplikasi Anestesi, 2019)
Diabetic ketoacidosis (DKA) is a syndrome of insulin deficiency and counterregulatory hormone excessthat causes excessive production of glucose and ketones, but their use is reduced, causing ketoacidosis and hyperglycemia. The purpose of this case report is to review the pathophysiology of DKA and the current management of DKA relevant to anesthesiologists, especially in intensive care unit (ICU) settings. DKA therapy includes adequate fluid requirements, restoration of metabolic consequences of insulin insufficiency, correction of electrolyte and acid-base imbalances, introduction of causes or triggers and treatment; and avoid complications. A better understanding of the pathophysiology of DKA and its aggressive and uniform approach to diagnosis and management has reduced mortality.